PENGARUH KECERDASAN SPRITUAL TERHADAP PENGENDALIAN DIRI SISWA DI MTSN 2 KOTA PAYAKUMBUH - Vivi Rahmawati; M.Arif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the phenomenon of students who do not understand spiritual intelligence, it is possible that this will affect students' self-control at MTsN 2 Kota Payakumbuh. This study aims to: (1) find out how the description or description of the spiritual intelligence profile is (2) find out how the description or description of the self-control profile is (3) find out how much influence spiritual intelligence has on self-control. This research is a field research using a quantitative approach. The population in this study were 351 students in grade Ⅷ. The sampling used the Stratified Random Sampling technique, so the number of samples was 151 students. Data were collected using a Likert scale questionnaire 4. Based on the results of the study, it is known that the hypothesis is accepted, this means that there is a very significant relationship between spiritual intelligence and self-control of students at MTsN 2 Kota Payakumbuh. From the results of the hypothesis, the Sig. (2-tailed) value is 0.252 because the Sig. (2-tailed) value <0.05, meaning that there is a significant relationship between the spiritual intelligence variable and self-control. Then the correlation coefficient number is obtained as much as 0.236, meaning the level of correlation strength or relationship is a sufficient or strong enough relationship. It can be concluded that there is a significant influence between spiritual intelligence and self-control. The hypothesis test value is obtained with a significance value of 0.000 ≤ 0.05. While the t count is known to be 6.778 ≥ 1.655.